Fresno County Bar Association Bernie Witkin Luncheon at the Fresno Hilton Hotel 2nd Floor Ballroom - Watkins, Howard::::::::: (1989)
Bernie Witkin giving his talk and assessment on recent U.S. Supreme Court decisions